Peta Aksesibilitas (Denpasar Accessible Map) Bagi Penyandang Disabilitas di Ruang Publik Kota: Menuju Kota Denpasar Ramah Disabilitas - Ni Luh Putu Eka Pebriyanti (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2020)
Inevitably, accessibility for priority users, such as children, the elderly, disabled and pregnant women, is a problem that is often found in public spaces in almost most major cities in Indonesia. The design of urban public spaces, such as city parks, malls and shops, pedestrian paths, markets, terminals, campuses or schools, has not made it easy for priority users to realize equal opportunities in all aspects of life, including accessibility to urban public spaces. The existence of the Denpasar City program towards a child-friendly, elderly-friendly city, green open space and towards a smart city encourages all parties to pay attention to facilities in the city's public spaces. Not only the Denpasar City Government attention but also academics are expected to be able to contribute to public space concepts that are accessible to all users. This study with the title: Accessibility Map (Denpasar Accessible Map) for Persons with Disabilities in City Public Spaces: Towards a Disability Friendly Denpasar City aims to help people with disabilities access public facilities and get the same services as other communities. The strategy is carried out by the use of information technology from the concept of the Smart City of the Denpasar City Government to socialize the empowerment program for persons with disabilities and to make the City of Denpasar Friendly with Disabilities (Inclusive Cities).